Effect of protonation on the nanoalloying of lithium niobate; Korus 2004; V. 3 - Borodin Y. V. (2004, 2004)
The results on protonation in solutions and melts of salts and acids, as well as structural changes associated with the formation of nanocomposition (NC) structure of materials are presented. The associated protonation is a necessary condition for proton separation of structural units (PSU) in NC structure model. The shape and size of PSU in simple substances and compounds and their variation in phase transition have been determined with the use of modified formula of cinematic diffraction theory applied to minimal scattering volumes. The possibilities of variation in PSU block size, interblock isotope exchange and proton-ionic nanoalloying by single and two valence ions have been demonstrated with regard to protonation regimes. A conclusion has been made that high content of interblock protons causes mechanical/chemical splitting in crystals.